The Intra-Montane basins of the midland zone, geological hazards with special reference to human activities - Sharma, Toran (Journal of Nepal Geological Society, 1992)
Intra-montane basins of the Midland zone are made up of Pli- Quaternary deposits and are represented by terrace landform which are still on the formative stages. Their geological environment is very delicate and unmindful land utilization could have an unrepairable consequences. Over the recent years, unmanaged land utilization practices have initiated a series of land degradational processes which are not conducive to the population thriving on the landform. This paper is an attempt to highlight the geological environment of the basins and also to point out how the socioeconomic activities are accelerating the geological hazards.